Kelas Utama Tanda Tanda Nonverbal pada Iklan PayPay - Sunjaya, Theresa; Irmayanti, Desy (Faculty of Letters, Dr. Soetomo University, 2021)
This study discusses the classification of the ten classes of nonverbal signs in Japanese video advertisement from PayPay. A nonverbal sign is a sign in the form of a picture or a gesture. In video advertising, the nonverbal signs are designed with the purpose to implicate a recommendation of the product shown. Therefore, it is suggested that using it as an object of research would be befitting. The nonverbal signs found in the advertisement will be classified into ten classes of signs through Peirce's semiotic theory. The result of this study is PayPay have many class types of ten classes of signs that contain the Firstness philosophy foundation. In PayPay, there is a total of five of ten classes of signs realized by 38 signs. The percentages of the classes are inclined toward Qualisign.